Conceptualizing Parenting Wisdom: Scale Development and Validation. Issue 4 (19th May 2022) - Boumpouli, Christina; Brouzos, Andreas; Vassilopoulos, Stephanos P.
Abstract: This paper introduces the construct of parenting wisdom and describes the development and preliminary validation of the Parenting Wisdom Scale (PWS), a new instrument designed to measure the construct. In a first study, a preliminary version of the PWS was developed and administered to a sample of 137 parents in Greece. The final version of the scale demonstrated the predicted four-factor solution and good internal consistency for the total and subscale scores. PWS correlated in expected ways with the convergent, discriminant and concurrent validity measures. In a second replication study, the above findings were cross-validated with an independent sample of 312 parents. In total, results are encouraging and seem to support the usefulness of the PWS to assess parenting wisdom.